Implications of State Policy Through Village Funds Towards the Cultural Values of Mutual Cooperation in the Village - Hariyanto Hariyanto (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
The state policy in the form of providing village funds will have an impact on the pattern of relations and relations between the village government and the village community, as well as among their own village communities. At least the implications of this will affect the values of the mutual cooperation culture in the village community. The present study aims to answer the state policy through village funds towards village autonomy and its implications for the values of mutual cooperation culture in the village of Kedungbanteng sub-district, Banyumas Regency. This research is a sociolegal study, using the methodological approach of the social sciences and the nature of the research used in this descriptive-analytical study. The research location was in the Kedungbanteng sub-district of Banyumas using a purposive sampling method.The results of the study show that the state policy through village funds when associated with village autonomy turns out that the village has autonomy called village autonomy where village autonomy is not given by the state but village autonomy comes from the village itself. Village government is given more space in managing its own household affairs. While the implication, although we cannot deny that the existence of village funds is also the least influencing eroded mutual cooperation culture in society, but this is not a dominant factor